IMPLEMENTASI KONSELING MULTIKULTUR DALAM MENANGGULANGI BULLYING - Khairunisa Khairunisa; Firman Firman; Riska Riska (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
Indonesia, as a multicultural country with diverse ethnicities, religions, teachings and understandings, opens opportunities for various understandings to influence it. The world of education is one of the potential targets for spreading the seeds of bullying. The notion of bullying pays attention to aspects of diversity (uniformity) and negates diversity (plurality). The condition of adolescence is a period that is vulnerable and sensitive to environmental influences. At this time, adolescents are identical with the period of identity and the desire to strengthen their philosophy of life. Guidance and counseling services are one of the services in the world of education that are very strategic in tackling the spread of bullying seeds. Counseling services through the concept of multiculturalism are considered indispensable in shaping the personality of teenagers who are able to respect each other in every difference. Therefore, this study intends to show that multicultural counseling is one way to foster civilized attitudes of students so that they are not trapped in the wrong understanding of differences.